Kenaf bast cellulosic fibers hierarchy: a comprehensive approach from micro to nano - Karimi, Samaneh; Md. Tahir, Paridah; Karimi, Ali; Dufresne, Alain; Abdulkhani, Ali (Elsevier, 2014)
Cellulosic fibers from kenaf bast were isolated in three distinct stages. Initially raw kenaf bast fibers were subjected to an alkali pulping process. Then pulped fibers undergone a bleaching process and finally both pulped and bleached fibers were separated into their constituent nanoscale cellulosic fibers by mechanical shearing. The influence of each treatment on the chemical composition of fibers was investigated. Moreover morphology, functional groups, crystallinity, and thermal behavior of fiber hierarchy at different stages of purification were studied using scanning and transmission electron microscopies, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and thermogravimetric analysis (TGA), respectively. Microscopy studies revealed that applied procedures successfully isolated nanoscale cellulosic fibers from both unbleached and bleached pulps. Chemical composition analysis and FTIR spectroscopy showed that lignin and hemicellulose were almost entirely removed by the applied treatments. XRD and TGA analyses demonstrated progressive enhancement of properties in fibers, hierarchically, in going from micro to nano scale. Interestingly no significant evolution was observed between obtained data of characterized ubnleached and bleached nanofibers.